Analisis Kesulitan Siswa Dalam Mengerjakan Soal Matematika Materi Perbandingan Kelas VII SMP Luhur Baladika - Nicky Maya Sari (IAIN BENGKULU, 2020)
Comparison material is the main thing in this research. Because the researcher wants to see the extent to which students understand comparative material. The main problem in this study is the difficulty of students in working on math problems. This study aims to analyze the students' difficulties in working on comparative matter questions. The method used is descriptive qualitative carried out at Luhur Baladika Middle School in the odd semester of the 2019/2020 school year. 26 students were taken as sample VII class. In this study, taking data with test results based on the number of questions as many as 5 items and interviews. Based on the results of the analysis and discussion in this study, it can be concluded that the types of difficulties made by VII grade students of SMP Luhur Baladika in working on comparative material mathematics problems are concept errors, procedural errors, and algotrima errors. The cause of students making mistakes in doing math problems in comparison material is students do not understand concepts, students cannot combine concepts needed to solve problems, student negligence factors, students do not understand the purpose of the questions and steps to solve problems. So in working on math problems comparative material students find it difficult to work on problems because students do not understand a comparative material concept that results in students doing wrong questions.